2021
DOI: 10.3390/ijerph18062989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cooperative Learning Intervention on the Intrinsic Motivation of Physical Education Students—A Meta-Analysis within a Limited Range

Abstract: This study was conducted to explore physical education students’ intrinsic motivation and clarify the influence mechanism of cooperative learning methods on learning intrinsic motivation through meta-analysis. In accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) criteria, we screened literature from the years 2000–2020. The included literature underwent bias analysis on the basis of the five criteria proposed herein. Data were extracted and summarized from the included literature to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 57 publications
(55 reference statements)
0
11
0
3
Order By: Relevance
“…Why did team work using cooperative learning techniques improve learning goals? Cooperative learning has considerable educational benefits, including intrinsic motivation, positive attitudes toward the subject, improved self-esteem, social support, group cohesion and participation ( Fernandez-Rio et al, 2017 ; Han and Son, 2020 ; Cecchini et al, 2021 ; Liu and Lipowski, 2021 ). Generally speaking, cooperative learning environments tend to be more dynamic, appealing and enjoyable, as well as giving students more responsibility and power over their learning, enhancing perceived autonomy and competence and making a significant contribution to improving learning goals ( Slavin, 1983 ; Johnson and Johnson, 1990 ; Amin, 2020 ; Han and Son, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why did team work using cooperative learning techniques improve learning goals? Cooperative learning has considerable educational benefits, including intrinsic motivation, positive attitudes toward the subject, improved self-esteem, social support, group cohesion and participation ( Fernandez-Rio et al, 2017 ; Han and Son, 2020 ; Cecchini et al, 2021 ; Liu and Lipowski, 2021 ). Generally speaking, cooperative learning environments tend to be more dynamic, appealing and enjoyable, as well as giving students more responsibility and power over their learning, enhancing perceived autonomy and competence and making a significant contribution to improving learning goals ( Slavin, 1983 ; Johnson and Johnson, 1990 ; Amin, 2020 ; Han and Son, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This requires effort, interest and recognition of the fact that the proper functioning of the teams and attainment of the learning objectives depend upon the teacher’s role, as does student satisfaction with group work. Cooperative learning is useful in addressing a lack of motivation for learning among students and it is viewed as a positive teaching methodology capable of motivating students in university settings ( Ovejero, 1993 ; van Wyk, 2012 ; Tran, 2019 ; Cecchini et al, 2021 ; Liu and Lipowski, 2021 ). Slavin (2014) identifies several theoretical perspectives on the effects of cooperative learning, including a motivational perspective emphasizing the incentives it provides for students to complete their academic work.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that collaborative learning and social interaction through elaboration with peer discussion can reduce intrinsic and extraneous cognitive load [34]. Also, it was suggested that during collaborative VPs, students could link new information and new knowledge with the old or prior knowledge (schemata) or even build new schemata in a better way with less intrinsic and extraneous cognitive loads [5,[23][24][25]35]. These studies attributed the efficiency of collaborative learning to several factors including a) the instructional design of VPs which containing simulated clinical scenario similar to the real practice, b) social discussion and elaboration with the peers and c) continuous feedback given to the student during the collaborative VPs session by the instructor.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative learning groups are effective when students work together to achieve common goals. By using strategies, which promote cooperation, participation, and student's interaction and problem solving (Quinquer, 2004;Tran, 2019;Liu and Lipowski, 2021), it is possible to approach current professional teaching training contexts from an academic environment. From this perspective, cooperative learning is not only a strategy or a methodology but also a learning content (Pujolás, 2008), essential in current teacher training.…”
Section: Theoretical Frameworkmentioning
confidence: 99%